Sector, globalization and urban economic growth: Evidence from Bangalore (India) - M. R. Narayana (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper aims at economic analysis of economic globalization and urban growth of Bangalore, the Silicon Valley of India, as they are related to ICT sector. Overall analyses offer new insights and evidences for ICT sector as a major contributor for degree of economic globalization and urban economic growth, mainly driven by ICT services. Bangalore's performance is remarkable compared to all-India level and OECD averages. These results offer empirical justification for continuing with and strengthening of public policies for promotion of globalizing and growth-oriented ICT sector in Bangalore with implications for comparable Indian and Asian cities.
Keywords: O18; R11; 330; globalization; ICT sector; urbanization; urban economic growth; Bangalore